Ruptured Rathke Cleft Cyst Mimicking Pituitary Apoplexy - Neidert, Marian Christoph; Woernle, Christoph Michael; Leske, Henning; Möller-Goede, Diane; Pangalu, Athina; Schmid, Christoph; Bernays, René-Ludwig (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Rathke cleft cysts (RCCs) are benign cystic lesions of the sellar and suprasellar region that are asymptomatic in most cases. Occasionally, compression of the optic pathway and hypothalamo-pituitary structures may cause clinical symptoms, such as headaches, visual deficits and endocrinopathies. Acute presentation caused by hemorrhage into an RCC have been described in the literature, and the term “Rathke cleft cyst apoplexy” has been coined. We present the case of a 32-year-old man with acute onset of meningitis-type symptoms and imaging findings resembling hemorrhagic pituitary tumor apoplexy. In retrospect, clinical symptoms, intraoperative appearance, and histologic examination were compatible with the diagnosis of nonhemorrhagic rupture of an RCC. Thus, the clinical presentation of “Rathke cleft cyst apoplexy” is not necessarily caused by hemorrhage.
Keywords: Rathke cleft cyst; pituitary apoplexy; sellar mass; RCC rupture; nonhemorrhagic RCC apoplexy